TRANSITIVITY IN THE TENTH GRADE STUDENTS’ RECOUNT TEXTS (A SYSTEMIC FUNCTIONAL GRAMMAR: SFG) - Sita Hediyati Rahayu; Efransyah Efransyah (IKIP Siliwangi, 2020)
This research aims to analyze the use of transitivity in the tenth grade students’ recount text and to find out the types of processes that are mostly found in the text. The data are taken from five recount texts written by five groups of the tenth grade students in one of the senior high schools in Cimahi. The researchers used descriptive qualitative as the method of this research. From the whole data, the researchers found 69 clauses and those are divided into seven types of processes as stated by Halliday. After classifying them, the researchers only found six types of processes which are: material process found in 45 clauses (65.2%), mental process found in 11 clauses (16%), relational process found in 5 clauses (7.2%), existential process found in 4 clauses (5.8%), behavioral process found in 2 clauses (2.9%) and verbal process found in 2 clauses (2.9%). While meteorological process was not found in the data. The most commonly process found in the data was material process which consists of 45 clauses for the recount text was retelling something happened in the past which experienced by the students. Keywords: Systemic Functional Grammar, Transitivity, Recount Text